2022
DOI: 10.3390/ijms232012553
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Genetic Studies on Powdery Mildew Resistance in TGR-1551

Abstract: Cucurbits powdery mildew (CPM) is one of the main limiting factors of melon cultivation worldwide. Resistance to races 1, 2, and 5 has been reported in the African accession TGR-1551, whose resistance is controlled by a dominant–recessive epistasis. The dominant and recessive quantitative trail loci (QTL) have previously been located in chromosomes 5 and 12, respectively. We used several densely genotyped BC3 families derived from the cross between TGR-1551 and the susceptible cultivar ‘Bola de Oro’ to finely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 80 publications
1
4
0
Order By: Relevance
“…Through the whole genome-based approach, these NBS-LRR or LRR genes were found to be putative candidate genes for Pm1 gene in Cannabis sativa [96]. Similarly, in another study NBS-LRR was reported to be putative candidate gene in melon against powdery mildew [69]. Hence, all these findings suggest that the F-Box gene may be the putative candidate gene and the marker developed in this study will be used in the marker assisted breeding programs.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Through the whole genome-based approach, these NBS-LRR or LRR genes were found to be putative candidate genes for Pm1 gene in Cannabis sativa [96]. Similarly, in another study NBS-LRR was reported to be putative candidate gene in melon against powdery mildew [69]. Hence, all these findings suggest that the F-Box gene may be the putative candidate gene and the marker developed in this study will be used in the marker assisted breeding programs.…”
Section: Discussionsupporting
confidence: 60%
“…A similar inheritance study was reported in resistant line, Zimbabwean melon TGR-1551 resistance against 1, 2 and 5 of P. xanthii. Based on the genetic analysis, it is reported to carry two independent genes, one dominant and one recessive [69]. Similarly, the PMR 5 resistant line carries a single dominant gene against race 5 of Px [70].…”
Section: Discussionmentioning
confidence: 99%
“…It is necessary to breed varieties with multiple race-specific resistance genes and field resistance genes, and to date, several genes and QTL associated with resistance to PM have been mapped in different melon populations derived from several genetic sources (Table 1, Haonan et al 2020). The identified QTLs have been listed by López-Martín et al (2022).…”
Section: Resistance To Other Diseasesmentioning
confidence: 99%
“…Identifried PM resistnce loci -like, has been identified on chromosome 5 as a candidate resistance gene(López-Martín et al 2022). Another P. xanthii resistance gene for races 1 and 3 (Pm-w WMR 29 ) has been identified in a cluster of nucleotide-binding leucinerich repeat receptors (NLRs) on chromosome 5.…”
mentioning
confidence: 99%
“…Melon ( Cucumis melo L.) is an economically important crop [ 1 ] and China is the largest melon producer, accounting for 51% of the global production [ 2 ]. Melon has been cultivated in Xinjiang for more than 2000 years and the region is currently the largest melon producing region in China [ 3 ].…”
Section: Introductionmentioning
confidence: 99%